MANUFACTURE OF A PORTABLE SINK TO PREVENT THE SPREAD OF COVID-19 AT THE ELEMENTARY SCHOOL, DARUL AMAN DISTRICT, EAST ACEH - munawir munawir; Rizalul Akram; Khairul Muttaqin (Global Science Society, 2021)
Since the arrival of the corona virus or covid-19 outbreak from the city of Wuhan, China, washing hands is very important, because the virus can easily enter the body through the mouth, nose and eyes. Therefore it is very important to wash your hands with soap or with an antiseptic before and after touching other objects, especially food. A portable sink is equipment used for washing hands, accompanied by using liquid soap as well so that germs, bacteria, and viruses die. The implementation of activities is carried out by making and providing portable sink assistance that are ready for use by schools through their respective school principals and also socializing its use at SD Negeri 1, SD Negeri 2, SD Negeri 5 and SD Negeri Bagok Panah Lhee Kec. Darul Aman, Idi, East Aceh. Community Service Activities have been carried out smoothly in the form of portable sink assistance. It is hoped that the school can make the best use of it and take care of it so that it can be used for a long time. In the future, it is hoped that it can provide even more assistance to schools in the form of other equipment for preventing Covid-19..